2014
DOI: 10.5312/wjo.v5.i4.516
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins and interleukin receptors in rheumatoid arthritis: Research, diagnostics and clinical implications

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease, resulting in a chronic, systemic inflammatory disorder. It may affect many tissues and organs, but it primarily affects the flexible joints. In clinical practice patient care generates many questions about diagnosis, prognosis, and treatment. It is challenging for health care specialists to keep up to date with the medical literature. This review summarizes the pathogenesis, the polymorphisms of interleukin and interleukin genes and the standard available and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 188 publications
(204 reference statements)
3
40
0
5
Order By: Relevance
“…Quantifying circulating IL-1b is not practical: it is virtually undetectable in human plasma even in patients with active CAPS 22 ; but elevated levels of both IL-6 and IL-18 have been observed in patients with rheumatoid arthritis, 23,24 Schnitzler syndrome, 20,25,26 and autoinflammatory diseases 27 and thus can be used as a sensitive marker of disease severity. IL-18, similar to IL-1b, requires processing by caspase-1 for its biological activation, whereas the production IL-6 is under tight control of IL-1b.…”
Section: Rowczenio Et Almentioning
confidence: 99%
“…Quantifying circulating IL-1b is not practical: it is virtually undetectable in human plasma even in patients with active CAPS 22 ; but elevated levels of both IL-6 and IL-18 have been observed in patients with rheumatoid arthritis, 23,24 Schnitzler syndrome, 20,25,26 and autoinflammatory diseases 27 and thus can be used as a sensitive marker of disease severity. IL-18, similar to IL-1b, requires processing by caspase-1 for its biological activation, whereas the production IL-6 is under tight control of IL-1b.…”
Section: Rowczenio Et Almentioning
confidence: 99%
“…Serum and synovial fluid levels of IL-6 and soluble IL-6 receptors (sIL6R) were found to be elevated in patients with RA [4]. IL-6 promotes the production of autoantibodies such as Rheumatoid Factor (RF) and Anti-Citrullinated Peptide Antibody (ACPA).…”
Section: Introductionmentioning
confidence: 99%
“…In 2017 Dinesh P et al 19 and reported role of IL-21 in rheumatoid arthritis pathogenesis, he also reported function of IL-21 in immune cells that promotes synovial destruction of cartilage and bone. Its involvement was also described in important signaling pathways.…”
Section: Discussionmentioning
confidence: 98%